An exploration of task based fMRI in neonates using echo-shifting to allow acquisition at longer TE without loss of temporal efficiency - Ferrazzi, Giulio; Nunes, Rita G.; Arichi, Tomoki; Gaspar, Andreia S.; Barone, Giovanni; Allievi, Alessandro; Vasylechko, Serge; Abaei, Maryam; Hughes, Emer; Rueckert, Daniel; Price, Anthony N.; Hajnal, Joseph V. (NeuroImage, 2016)
Optimal contrast to noise ratio of the BOLD signal in neonatal and foetal fMRI has been hard to achieve because of the much longer T2* values in developing brain tissue in comparison to those in the mature adult brain. The conventional approach of optimizing fMRI sequences would suggest matching the echo time (TE) and the T2* of the neonatal and foetal brain. However, the use of a long echo time would typically increase the minimum repetition time (TR) resulting in inefficient sampling. Here we apply the concept of echo shifting to task based neonatal fMRI in order to achieve an improved contrast to noise ratio and efficient data sampling at the same time. Echo shifted EPI (es-EPI) is a modification of a standard 2D-EPI sequence which enables echo times longer than the time between consecutive excitations (TE>TS=TRNS, where NS is the number of acquired slices and TS the inter-slice repetition time). The proposed method was tested on neonatal subjects using a passive sensori-motor task paradigm. Dual echo EPI datasets with an identical readout structure to es-EPI were also acquired and used as control data to assess BOLD activation. From the results of the latter analysis, an average increase of 78 ± 41% in contrast to noise ratio was observable when comparing late to short echoes. Furthermore, es-EPI allowed the acquisition of data with an identical contrast to the late echo, but more efficiently since a higher number of slices could be acquired in the same amount of time.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Contrast to noise ratio; Echo shifting; Neonatal fMRI